2015
DOI: 10.1111/1348-0421.12318
|View full text |Cite
|
Sign up to set email alerts
|

Gut feelings of safety: tolerance to the microbiota mediated by innate immune receptors

Abstract: To enable microbial colonization of the gut mucosa, the intestinal immune system must not only react to danger signals but also recognize cues that indicate safety. Recognition of safety, paradoxically, is mediated by the same environmental sensors that are involved in signaling danger. Indeed, in addition to their well-established role in inducing inflammation in response to stress signals, pattern recognition receptors and a variety of metabolic sensors also promote gut-microbiota symbiosis by responding to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 127 publications
(141 reference statements)
0
34
0
Order By: Relevance
“…It is recognized that the host immune system promotes the residence of commensal bacteria in healthy animals (Swiatczak & Cohen, ). In this study, the expression of TLR2, TLR5, and MyD88 was increased, but the expression of IL‐1β and IFN‐γ was decreased by the butyrate infusion.…”
Section: Discussionmentioning
confidence: 99%
“…It is recognized that the host immune system promotes the residence of commensal bacteria in healthy animals (Swiatczak & Cohen, ). In this study, the expression of TLR2, TLR5, and MyD88 was increased, but the expression of IL‐1β and IFN‐γ was decreased by the butyrate infusion.…”
Section: Discussionmentioning
confidence: 99%
“…The guts and the gut immune systems of mammals, for example, are equipped with receptors that accommodate symbiotic microbiota and distinguish them from microbial pathogens 37 ; indeed, the tolerance of the immune system towards symbiotic microbiota highlights the impossibility of defining an immutable “immune self” – the “self” is an interactive process rather than a closed entity 24, 38 ; in fact, the individual immune system is an ecosystem of interacting cells 39 . Struggles between predators and prey are organized by sight, smell and taste receptors that mark what should be hunted and eaten by the predators and avoided by the prey: mice and cats, for example, innately recognize one another; zebras and lions signal each other clearly to establish a stable equilibrium between hunters and hunted 40 .…”
Section: The Mechanism Of Entropic Selectionmentioning
confidence: 99%
“…Preliminary studies also indicated that infections with C. suis alter the succession of bacterial communities in neonatal pig gut, delaying the establishment of lactobacilli (as reviewed in [37]). As interactions between microbiota and the immune system are key to the development of a functional immune system [40] such events may have lasting effects on the development of intestinal and immune functions. As such alterations have been described for other intestinal parasitic infections [21], a role of intestinal parasitic infections in gut health should be re-evaluated in pigs, too.…”
Section: Background - Vaccines Against Parasitesmentioning
confidence: 99%